Adaptive Discretion in Child Marriage Prevention: Street-Level Bureaucracy in Indonesia’s Islamic Marriage Administration - Noorhaidi Hasan; Moh. Mufid; Nina Mariani Noor; Halili Rais; Zezen Zainul Ali (Institut Agama Islam Negeri (IAIN) Pontianak, 2026)
The increase in the minimum age of marriage through Law No. 16 of 2019 represents a landmark reform in Islamic family law in Indonesia. However, the high number of marriage dispensation cases suggests that this statutory change has not automatically resulted in effective child protection. This article argues that preventing child marriage depends less on legislative reform and more on the discretionary practices of religious bureaucrats at the street level. Employing a socio-legal approach and a mixed-methods design, the study integrates a Knowledge, Attitudes, and Practices (KAP) survey, field observations, in-depth interviews, and focus group discussions conducted at four Offices of Religious Affairs (KUA) in the Special Region of Yogyakarta and Central Java. The findings reveal a pattern of normative ambivalence in defining maturity—between the legal age threshold and the fiqh (Islamic jurisprudence) concepts of ʿāqil (intellect) and bāligh (puberty)—reflecting a broader configuration of legal pluralism among state law, fiqh, and local norms. Nevertheless, most KUA officials demonstrate a substantive commitment to child protection through practices of adaptive discretion, normative mediation, and legal counseling in their roles as street-level bureaucrats. This article advances legal pluralism theory by demonstrating that normative negotiation occurs not only in society but also within state bureaucratic institutions, where Islamic family law is actively produced and operationalized as law in action. Ultimately, child protection in a plural legal order hinges on how institutional discretion is governed, embedded in, and negotiated through shifting configurations of authority among the state, religious actors, and local communities. [Kenaikan batas usia minimum perkawinan melalui Undang-Undang No. 16 Tahun 2019 merupakan tonggak penting dalam reformasi hukum keluarga Islam di Indonesia. Namun, tingginya jumlah permohonan dispensasi kawin menunjukkan bahwa perubahan normatif tersebut belum secara otomatis bertransformasi menjadi perlindungan anak yang efektif. Artikel ini berargumentasi bahwa pencegahan perkawinan anak lebih ditentukan oleh praktik diskresi birokrasi keagamaan di tingkat garis depan dibandingkan oleh reformasi legislasi semata. Dengan menggunakan pendekatan sosio-legal dan desain metode campuran, penelitian ini mengintegrasikan survei Pengetahuan, Sikap, dan Praktik (KAP), observasi lapangan, wawancara mendalam, serta diskusi kelompok terfokus yang dilaksanakan di empat Kantor Urusan Agama (KUA) di Daerah Istimewa Yogyakarta dan Jawa Tengah. Temuan penelitian mengungkap pola ambivalensi normatif dalam memaknai kedewasaan—antara ambang batas usia legal dan konsep fikih tentang ʿāqil (kemampuan intelektual) dan bāligh (pubertas)—yang merefleksikan konfigurasi pluralisme hukum antara hukum negara, fikih, dan norma sosial lokal. Meskipun demikian, sebagian besar pejabat KUA menunjukkan komitmen substantif terhadap perlindungan anak melalui praktik diskresi adaptif, mediasi normatif, dan konseling hukum dalam perannya sebagai birokrat tingkat jalanan. Artikel ini memperluas teori pluralisme hukum dengan menunjukkan bahwa negosiasi normatif tidak hanya berlangsung di ranah sosial, tetapi juga di dalam institusi birokrasi negara, tempat hukum keluarga Islam secara aktif diproduksi dan dioperasionalkan sebagai hukum dalam praktik. Pada akhirnya, efektivitas perlindungan anak dalam tatanan hukum plural sangat bergantung pada bagaimana diskresi institusional diatur, ditanamkan, dan dinegosiasikan dalam konfigurasi otoritas yang terus berubah antara negara, aktor keagamaan, dan komunitas lokal.]